2000
DOI: 10.1034/j.1600-0536.2000.043004212.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposures to cobalt or chromate on the hands of patients with hand eczema and contact allergy to that metal

Abstract: The present study aimed at evaluating the effects of daily repeated exposures to low cobalt or chromate concentrations on the hands of patients with hand eczema and cobalt or chromate allergy. For 2 weeks, the patients immersed a finger for 10 min daily into the appropriate metal salt solution in water. During the 1st week, this was a 10 or 50 mg/l cobalt concentration or a 10 mg/l chromate concentration, and, during the 2nd week, a 100 or 200 mg/l cobalt concentration or a 100 mg/l chromate concentration. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Also, the permeation of both nickel and cobalt ions may be closely associated with the oxidizing capacity of sweat (48, 60). It was recently demonstrated that cobalt and nickel powders penetrate damaged skin more easily than intact skin (61–65).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the permeation of both nickel and cobalt ions may be closely associated with the oxidizing capacity of sweat (48, 60). It was recently demonstrated that cobalt and nickel powders penetrate damaged skin more easily than intact skin (61–65).…”
Section: Introductionmentioning
confidence: 99%
“…Banfield et al found that one nickel allergic patient reacted to a lower nickel concentration on the hand than on the back (151). Nielsen et al investigated whether it could be assumed that nickel or cobalt exposure was a contributing factor of hand eczema (63, 64). In a double‐blind placebo controlled exposure study, a statistically significant aggravation of hand eczema was observed when patients with nickel allergy and mild to moderate hand eczema were exposed to 10–100 ppm nickel for 10 min per day over a 2‐week period (63).…”
mentioning
confidence: 99%
“…The sweat solutions (incubated with Cr(III), incubated with Cr(VI) and blank) were incubated at 377C for 22 h with constant shaking and then analyzed with CE-ICP-SF-MS. Concentrations of incubated Cr(III) and Cr(VI) (dichromate) ranging from 1 to 500 mg?L 21 were investigated, in agreement with concentrations used in dose-response investigations [2,13,[28][29][30][31]. The experimental conditions of the CE-ICP-SF-MS setup are summarized in Table 1.…”
Section: Detection Of Chromium Species After Incubation Of Simulated mentioning
confidence: 99%
“…Zn from an industrial exposure (galvanizing) or from the use of Zn-based creams elevated Zn-TN in normal healthy adult students of New Zealand (McKenzie 1979). Accumulation of cobalt or chromate in the nails has been demonstrated during daily repeated exposure to low cobalt or chromate concentrations by immersing fingers for 10 min (S01) d for 2 wk (Nielsen et al 2000). The free surface of nails adsorbs a considerable quantity of Ca from the environment, and it is reasoned that such adsorption occurs due to ion exchange; this is evident from the fact that sulfur does not vary over nail cross sections (Forslind et al 1976).…”
Section: Contaminationmentioning
confidence: 99%